«Печера між скель» на шляху турецького війська у Хотинській війні 1621 р. - Ільків, Микола; Ilkiv, Mykola (Фортеця: збірник заповідника «Тустань», 2022)
The comparison of data from different categories of sources is made. The way of movement of the Zaporozhian and Turkish armies in the Prut-Dniester interfl uve is detailed and the localization of one of the battles on the approaches to Khotyn was proposed – near the Bukovynka cave (Stalnivtsi, Chernivtsi region). Further elaboration of sources, fi eld research (primarily archaeological) will clarify the location and characteristics of the various objects at the Prut-Dniester theater of operations of the Khotyn War.
Keywords: Khotyn War, 1621, Zaporozhian and Turkish armies, Prut-Dniester interfl uve, Bukovynka cave